KEPENARIAN GULU DALAM TARI SRIMPI LUDIRAMADU GAYA SURAKARTA - Aqueenes Forsa Putri Setiawan; Dwi Rahmani (Greget, 2020)
Essay of this artwork present an analysis dizziness of Gulu’s in a Srimpi Ludiramadu dance Surakarta sytle covers problem 1). How was the dizziness of Gulu’s in the Srimpi Ludiramadu dance?, 2). How does the garap fillings and shapes of Srimpi Ludiramadu dance the dizziness of the Gulu’s?, 3). How was Gulu’s role in Srimpi Ludiramadu dance?. The three issues are discussed of the normatical concept of the Javanese Hasta Sawanda and the consept of garap fillings and shapes. The methods of art were conducted through library studies, observation, and interviews. Research has shown that the dizziness Gulu’s in a Srimpi Ludiramadu dance is required a process whish is countinue and intensive. Dancing a group dance must be supported by personal and group consciousness. The dizziness of the Gulu’s on this Srimpi Ludiramadu was taste of mrabu, kenes, and meneb supported with makeup and karawitan to keep up the impression of grace.                                                                                                                      Keywords: Dizziness, garap, Srimpi Ludiramadu.